1992
DOI: 10.1002/1097-0142(19921115)70:10<2488::aid-cncr2820701016>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Phase III trial of cyclophosphamide versus cyclophosphamide, doxorubicin, and methotrexate in hormone-refractory prostatic cancer: A hoosier oncology group study

Abstract: Background. Between August 1984 and November 1989, the Hoosier Oncology Group conducted a Phase III study comparing cyclophosphamide (CTX) with cyclophosphamide, doxorubicin, and methotrexate (CAM) in patients with hormone‐refractory metastatic prostatic cancer to determine whether the addition of doxorubicin and methotrexate to the cyclophosphamide regimen conferred any survival advantage. Methods. One hundred three patients were registered and randomized, 99 were evaluable for response, and all were evaluabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The development of androgen-insensitive prostate cancer metastasis represents the ®nal common pathway for patients dying of prostate cancer. DOX often produces transient responses in such patients [42,43,45] but, unfortunately, the vast majority of patients with androgen-insensitive metastases die of the disease [42±47]. We hypothesized that the development of drug-resistant prostate cancer cells could be related to the emergence of a highly undifferentiated state and that preventing the development of the dedifferentiated phenotype might be a relevant therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The development of androgen-insensitive prostate cancer metastasis represents the ®nal common pathway for patients dying of prostate cancer. DOX often produces transient responses in such patients [42,43,45] but, unfortunately, the vast majority of patients with androgen-insensitive metastases die of the disease [42±47]. We hypothesized that the development of drug-resistant prostate cancer cells could be related to the emergence of a highly undifferentiated state and that preventing the development of the dedifferentiated phenotype might be a relevant therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Today, multiple drugs targeting enzymes within the folate cycle are FDA-approved to treat a variety of cancer types [15]; however, these drugs have had mixed reports for the treatment of PCa. While early studies indicated that the antifolate, MTX, might have been beneficial in the treatment of CRPC, subsequent studies failed to support the original findings [213,214,215]. Because AR inhibition during ADT decreases polyamine synthesis, which may in turn increase methyl group availability in the folate cycle, it has been suggested that MTX may be more beneficial in the treatment of PCa at earlier stages of the disease [63,160].…”
Section: Therapeutic Approaches To Prostate Cancer: Targeting the mentioning
confidence: 99%
“…Oral cyclophosphamide is active against CRPC both alone and in combination regimens 19 , and vincristine has modest single-agent activity against it. 20 Dexamethasone has significantly reduced PSA levels, and a substantial percentage of patients whose PSA decreased also had radiographic evidence of disease regression 21 , as did our patient.…”
Section: Discussionmentioning
confidence: 99%